2020
DOI: 10.22541/au.159200526.62960408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac function in gestational diabetes mellitus: A longitudinal study from fetal life to infancy

Abstract: Objective: To determine whether cardiac functional and structural changes in fetuses of mothers with gestational diabetes mellitus (GDM) persist in the offspring beyond the neonatal period. Design: Longitudinal study Setting: Fetal Medicine Unit in a UK teaching hospital Population: 73 women with GDM and 73 women with uncomplicated pregnancy were recruited and fetal cardiac scans were performed at 35-36 weeks' gestation. Repeat echocardiogram was performed in their offspring during infancy. Main outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Screening for fetal cardiac malformation in the early second trimester is accurate [5] , and it is feasible and clinically signi cant to move the time window of prenatal diagnosis of fetal congenital heart disease forward. A large number of studies have shown that fetal cardiac function evaluation has important clinical value in the management and prognosis of gestational hypertension, gestational diabetes mellitus, and fetal congenital heart disease, among other diseases [6][7][8][9] . However, most studies have focused on the ultrasound assessment of fetal cardiac structure and function in the second or third trimesters, while few studies have focused on fetal cardiac function before 18 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Screening for fetal cardiac malformation in the early second trimester is accurate [5] , and it is feasible and clinically signi cant to move the time window of prenatal diagnosis of fetal congenital heart disease forward. A large number of studies have shown that fetal cardiac function evaluation has important clinical value in the management and prognosis of gestational hypertension, gestational diabetes mellitus, and fetal congenital heart disease, among other diseases [6][7][8][9] . However, most studies have focused on the ultrasound assessment of fetal cardiac structure and function in the second or third trimesters, while few studies have focused on fetal cardiac function before 18 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%